Record of margay (Leopardus wiedii) in a periurban Ecological Reserve in the central mountain region of Veracruz, Mexico - Villafañe-Trujillo, Álvaro José; Delfín-Alfonso, Christian Alejandro (Therya Notes, 2025)
Biodiversity worldwide is affected by human activities, species that inhabits in Protected Natural Areas are not exempt to human impact. Habitat resources are limited, species that requires large territories and a constant food availability cannot survive for long. The objective of this work is to point out and describe the occasional record of a specimen of margay (Leopardus wiedii) as a result from a systematic long-term survey in the periurban Ecological Reserve “La Martinica”, in the central mountainous area of the state of Veracruz (Mexico). For about 25 months (May 2021 to June 2023), a non-invasive survey focused on terrestrial and arboreal mammals was deployed in “La Martinica”. The camera traps were installed at ground (terrestrial stations) and in the canopy (arboreal stations), with an average distance of 300 m between them. The 24-hour cycles in which each camera operated correctly and uninterruptedly were considered 1 trap-day. After a sampling effort of 2,525 trap days, and an effective sampling area of 0.5 km2, in January 2023, at an altitude of 1,553 m, a specimen of margay was recorded in “La Martinica”. Due to the presence of other carnivores (exotic, introduced, and native) and the scarce mammal diversity at the study site (n =12 species), it is unlikely that a resident population of Leopardus wiedii inhabit in the region. The specimen was probably passing through during its dispersal. This record is the northernmost of the species obtained through systematic monitoring in the state of Veracruz.